Rutting Prediction of a Reinforced Cold Bituminous Emulsion Mixture Using Finite Element Modelling. (2016) - Shanbara, Hayder Kamil; Ruddock, Felicite; Atherton, William
Abstract: A three-dimensional (3D) finite element (FE) model of a reinforced cold bituminous emulsion mixture (CBEM) was built in order to investigate the effect of static wheel load on rutting formation and flexible pavement response. This model was developed to represent a four-layer pavement structure with elastic responses and to simulate the mechanical behaviour and pavement performance under static load condition. Also, it is focused on the prediction of the contribution of glass fibre (as a reinforcement material) in the surface course to the development of the tensile and shear strength of flexible pavements. The preparation and validation of the model were carried out in the pavement laboratory using experimental data. In this research, finite element analyses have been conducted using ABAQUS software, in which model dimensions, element types and meshing strategies are employed to achieve the desired degree of accuracy and convergence of the developed model. In addition, this developed model has been applied to CBEMs to investigate the effects of glass fibre on the performance of a reinforced pavement surface layer, as well as to study the effects of this fibre in terms of minimizing the vertical surface deflection, and horizontal and vertical displacements for the various courses. Finally, the FE model is capable of predicting surface damage to flexible pavements and their partial recovery following the application of the load. The results demonstrate the capability of the model to simulate the effect of fibre on vertical surface deflection (rutting), horizontal and vertical displacements in CBEM.